The Implementation of Skopos – Vermeer Theory in Translating Moral, Symbolism, and Cultural Messages in the Short Story Fatima und der Traumdieb by Rafik Schami - Andrias Setia Pribadi; Rosyidah (Nexus Publishing, 2025)
This study aims to describe the application of Skopos Theory by Vermeer Theory in translating elements of moral messages, symbolism, and culture in the short story Fatima und der Traumdieb by Rafik Schami. This research is a descriptive qualitative study involving 9 students of the Einführung in die Übersetzungswissenschaft course at the UM German Language Education Study Program as research subjects. The primary instruments were obtained through student translation tasks and analyzed using an interactive model, with the researcher serving as the main instrument and utilizing a documentation table. Findings indicate that while Skopos Theory facilitates more target-oriented and acceptable translations, 91 out of 162 translated items were found to be inappropriate. These inaccuracies stem primarily from students’ limited understanding of contextual meaning, pragmatic nuances, and grammatical structures. The study concludes that although Skopos Theory is effective in guiding the translation of literary texts, mastery of contextual and cultural understanding is essential to ensure accurate message delivery. It is recommended that additional translation training be provided, particularly in dealing with complex moral, symbolic, and cultural content.